Evaluation of Tacrolimus Combined With Corticosteroids vs Modified Ponticelli Regimen as Treatments for Refractory Primary Membranous Nephropathy (2018)
Objective: To evaluate the immunosuppressive treatment response to modified Ponticelli regimen (MPR) and oral corticosteroid (OC) plus tacrolimus (TAC) in patients with primary membranous nephropathy (PMN). Methods: Retrospective cohort analytical study. Adults patients (>18 years old) with diagnosis of refractory PMN (>50% increase in serum creatinine or a level >1.5mg/dl or proteinuria refractory to 6 months of supportive treatment), proved by renal biopsy and immunofluorescence between 2008 and 2016 from the Nephropathy Registry of Colombia (NEFRORED©) were included. Immunosuppressive treatment response was evaluated from baseline to 6 months after the start of therapy. Results: 128 patients with PMN were included, of which 74 (57%) were female. The most frequent syndromic diagnosis was nephrotic syndrome 90 (70%), followed by asymptomatic urinary disorders 31 (25%). Chronic kidney disease manifested concomitantly in 7 (5%) patients. At the end of 6 months, 86 (67%) cases achieved some degree of remission: 23 (18%) complete response (CR) and 63 (49%) cases with partial response (PR), while 42 (33%) cases did not achieved remission. In the TAC+OC group, CR and PR were seen in 14 (20%) and 33 (47%) patients, respectively; and 9 (16%) and 30 (51%) patients in the MPR group, respectively. No statistically significant differences were found when comparing the immunosuppressive treatment response rate with both treatment groups (p > 0.05). Conclusions: In the PMN, both immunosuppressive treatments (TAC+OC vs MPR) are comparable. We suggest a clinical follow-up of the anti-PLA2R/THSD7A titres at 6/12 months to be correlated with renal function in subsequent studies.